STUDIES ON BIOLOGY AND BIOMETRY OF EPILACHNA BEETLE, EPILACHNA VIGINTIOCTOPUNCTATA FABRICIUS (COCCINELLIDAE: COLEOPTERA) ON BRINJAL IN WEST BENGAL, INDIA - S. P. BINDU; A. PRAMANIK (The Bioscan, 2015)
Studies on the biology of Epilachna beetle, Epilachna vigintioctopunctata revealed that the incubation period was 3.2 ± 0.84 days. The total larval period was 20.8 ± 3.35 days. The mean pupal period was 3.8 ± 0.84 days, measured 12.34±1.67 mm length and 4.40±0.47 mm in breadth. The mean adult male beetle longevity was 33.6 ± 2.70 days, recorded 5.93 ± 0.54 mm in length and 4.35 ± 0.34 mm in breadth. The mean lifespan of female beetle of E. vigintioctopunctata was observed 38.4 ± 1.52 days, measured 6.87± 0.59 mm in length, 5.23 ±0.63 mm in breadth. The duration of total life cycle varied 62.4 ± 7.13 days. The mean fecundity was recorded as 55.8 ± 7.73 eggs / female, the size eggs of Epilachna beetle was recorded as 1.05±0.24 mm in length and 0.41±0.08 mm in breadth. The body measurements of E. vigintioctopunctata of the life stages revealed that the adult female is slightly larger than male.